2018
DOI: 10.1021/acs.iecr.8b00094
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Attapulgite Nanorods with Nitrile Butadiene Rubber via Thiol–Ene Interfacial Click Reaction: Grafting or Crosslinking

Abstract: A versatile approach was developed for the preparation of cross-linked attapulgite (ATP)-nitrile butadiene rubber (NBR) nanocomposites or NBR grafted ATP nanorods, by facilely adjusting the feeding ratio between the butadiene-based rubbers and the thiol-modified attapulgite (ATP-SH) nanorods in a facile thermal-triggered thiol–ene interfacial click reaction. The modified products with different feeding ratios between the ATP-SH and NBR were characterized with FT-IR, TGA, and TEM techniques. The results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Zou et al [143] concluded that click-chemistry reactions, including selective and orthogonal reactions under mild conditions, had the potential to generate real stimuli not only in developing bioactive materials of choice, but also in making the leap to the industrial scale build-up of multifunctional products such as polymer-nanoclay composite scaffolds. Pan et al [144] developed a versatile approach based on facile thermal-triggered thiol-ene interfacial click-chemistry reactions for the preparation of nitrile butadiene rubber (NBR)/attapulgite nanoclay composites. The results indicated that the composites could be produced via the thiol-ene interfacial click reaction with excess NBR and potential use in the rubber industry.…”
Section: Click Coupling Chemistrymentioning
confidence: 99%
“…Zou et al [143] concluded that click-chemistry reactions, including selective and orthogonal reactions under mild conditions, had the potential to generate real stimuli not only in developing bioactive materials of choice, but also in making the leap to the industrial scale build-up of multifunctional products such as polymer-nanoclay composite scaffolds. Pan et al [144] developed a versatile approach based on facile thermal-triggered thiol-ene interfacial click-chemistry reactions for the preparation of nitrile butadiene rubber (NBR)/attapulgite nanoclay composites. The results indicated that the composites could be produced via the thiol-ene interfacial click reaction with excess NBR and potential use in the rubber industry.…”
Section: Click Coupling Chemistrymentioning
confidence: 99%
“…1b clearly shows the occurrence of unsaturated double bonds according to its blending absorption band of trans -CHvCHat 964 cm −1 and stretching vibration band at 1656 cm −1 . 41,42 The band at 1720 cm −1 belongs to the symmetrical stretching vibration of the CvO group. According to the EDS analysis, as shown in Fig.…”
Section: Modification and Characterization Of Wnrpsmentioning
confidence: 99%
“…(iii) Near 450 °C, ATP loses its complete structure and the ATP nanorods are dehydroxylated and decomposed at this temperature. 31,32 The TGA curve of the original UIO-66 (Fig. 6c) shows three stages of severe weight loss: (i) the first loss of weight near 50 °C is the small amount of residual methanol solvent in UIO-66; (ii) 248.2 °C is associated with the loss of unreacted joints (TPA) in the MOF pores; and (iii) the loss at 561 °C is assigned to the corresponding collapse of the UIO-66 structure and lattice degradation to CO 2 , CO, and ZrO 2 .…”
Section: Dalton Transactions Papermentioning
confidence: 99%